2020
DOI: 10.3390/cancers12040897
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Y90 Radioembolization Plus Sorafenib and Y90 Radioembolization alone in the Treatment of Hepatocellular Carcinoma: A Propensity Score Analysis

Abstract: Background: Adjuvant sorafenib may enhance the efficacy of transarterial radioembolization with yttrium-90 in hepatocellular carcinoma patients. The aim of this study is to assess the efficacy and safety of radioembolization plus sorafenib in comparison to radioembolization alone. Methods: Out of 175 hepatocellular carcinoma (HCC) patients treated with radioembolization between 2011 and 2018, after propensity score matching, two groups were compared: a group of 45 patients that underwent radioembolization whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In addition, it is not possible to establish whether the acceleration of the natural decay of the existing vasculature, suggested by the modeling analysis in CR, was due solely to sorafenib or to other concomitant conditions. In Case 1, for instance, tumor shrinkage was accompanied by complete atrophy of the left liver lobe, and we cannot rule out that the left branch portal vein thrombosis ( Figure 1 ) and the previous TARE may have played a role in tumor de-vascularization obtained by systemic treatment [ 32 , 33 ]. Overall, portal vein thrombosis was present in half of the patients analyzed, and we cannot exclude the possibility that changes of liver hemodynamics could have interfered on model parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is not possible to establish whether the acceleration of the natural decay of the existing vasculature, suggested by the modeling analysis in CR, was due solely to sorafenib or to other concomitant conditions. In Case 1, for instance, tumor shrinkage was accompanied by complete atrophy of the left liver lobe, and we cannot rule out that the left branch portal vein thrombosis ( Figure 1 ) and the previous TARE may have played a role in tumor de-vascularization obtained by systemic treatment [ 32 , 33 ]. Overall, portal vein thrombosis was present in half of the patients analyzed, and we cannot exclude the possibility that changes of liver hemodynamics could have interfered on model parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Among 112 patients, who received for at least 3 months of TKI treatment for BCLC-B (33) or BCLC-C (79) HCC at the Hepatology Unit of the Azienda Ospedaliera-Universitaria Pisana from 2007, we initially identified three cases who had clinically relevant responses and sufficient imaging and serological data for developing the mathematical model: Case-1 with CR to sorafenib, Case-2 with partial response to sorafenib and Case-3 with PR to regorafenib. Their detailed clinical features and the modeling analysis are reported in the Results section.…”
Section: Patientsmentioning
confidence: 99%
“…6 In a retrospective propensity score analysis, the outcomes of HCC patients (BCLC B-C) who received Y90 only (n ¼ 90) were compared with those who received sorafenib plus Y90 (n ¼ 45). 7 In the combined group, the median time on sorafenib prior to Y90 was 2 months, for a total median duration of therapy of approximately 9 months. The median daily dose of sorafenib was 800 mg.…”
Section: Hepatocellular Carcinoma Sorafenibmentioning
confidence: 96%
“…Based (32,33). As to the combination of sorafenib with TARE, a retrospective study suggested that no significant differences in survival outcomes were identified between sorafenib plus TARE and TARE monotherapy (median overall survival 10 vs. 10 months; p = 0.711) (34). Albeit the uncertainty of www.biosciencetrends.com BioScience Trends Advance Publication P4 vein invasion accounted for 55% and 23% of patients with HCC in the China cohort, respectively (37).…”
Section: The Mdt Of West China Hospitalmentioning
confidence: 99%